Standing Crop, Turnover, and Production Dynamics of Macrocystis pyrifera and Understory Species Hedophyllum nigripes and Neoagarum fimbriatum in High Latitude Giant Kelp Forests - Bell, Lauren E (Journal of phycology, 2022)
© 2022 The Authors. Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.